Richard Rand 50th anniversary volume - Gurran, Ardéshir (World Scientific, 1997)
"Consists of a collection of articles, dedicated to Richard Rand, Professor of Theoretical and Applied Mechanics at Cornell, on the occasion of his fiftieth birthday on June 8, 1993"--Page vii.; Includes bibliographical references and indexes.